GREEN INNOVATION: OPTIMIZING THE POTENTIAL OF PLASTIC WASTE AS AN ALTERNATIVE TO FOSSIL FUELS - Alfiyani, Hani; Gusmayanti, Evi; Wahyuni, Nelly (Journal of Environmental Science and Sustainable Development, 2025)
Plastic bag waste has the potential to be converted into alternative fuel oil through the pyrolysis method. This study applies the principle of thermal pyrolysis, conducted without oxygen, at the Edelweis Integrated Waste Management Site. The purpose is to analyze the characteristics of fuel oil derived from plastic bag waste based on parameters such as density, viscosity, calorific value, and acid number, as well as to estimate the potential fuel oil yield from plastic bag waste in Pontianak City. The results show that the density, viscosity, and calorific value of the produced fuel oil meet or closely approach standard requirements. However, the acid number measurements exceed the acceptable limits, 0.75 mg KOH/g for gasoline, 0.94 mg KOH/g for kerosene), and 0.50 mg KOH/g for diesel. This is likely due to high levels of chlorine (Cl) and silicon (Si) detected through X-Ray Fluorescence (XRF), which may originate from the plastic materials and red soil used as an adsorbent. Gas Chromatography-Mass Spectrometry (GC-MS) analysis confirms that the fuel oil contains hydrocarbon compounds similar to those found in commercial fuels, though in different proportions. Before the implementation of Circular Letter (CL) Number 43 of 2024, which prohibits businesses from providing plastic bags, the potential fuel oil production is estimated at 1,048,923.59 liters in 2024 and 1,259,375.52 liters in 2045. If this policy is fully implemented, fuel oil production is expected to decrease by approximately 16.52 percent in 2025 and 22.68 percent in 2045, due to the reduced use of plastic bags. This approach could be an effective way to reduce dependence on fossil fuels an estimated by 1 to 1.5 percent in 2025 and 0.8 to 1.7 percent in 2045. Although the results are promising, further testing is necessary to ensure full compliance with fuel standards.